Web semântica: uma análise focada no uso de metadados - Alves, Rachel Cristina Vesú [UNESP] (2005)
Nowadays our society, named society of information, has been characterized by the valorization of information through the increasing use of the information and communication technologies and the exponential growth of the informational resources, available in various environments, mainly on the Web. This reality has brought some changes for the automated access to information. If we have a big amount of informational resources available at one side, on the other we have problems related to search, localization, access and recuperation of this information in digital environments as a consequence. In this context, the problem that originated this research is related to the difficulty on searching and recuperating digital informational resources on the Web, and the lack of adequate treatment for the informational representation of these resources. At the moment, the biggest challenge for the scientific community is to identify patterns and methods of representation of information, that is, the construction of forms of representation of the informational resource in order to provide its search and recuperation in a more efficient manner. So, the pointed proposition for the solution of the problem, in this paper, refers to the Semantic Web establishment and the application of metadata patterns to the representation of information, because they are considered an important initiative for providing a better structuring and representation of the informational resources in digital environments. With a methodology based on the exploratory and descriptive analysis of the theme, beginning from the available literature, it is possible to present a Semantic Web analysis as a new proposal for the organization of the informational resources on the Web, and the technological tools that permeate its construction, focusing the use of metadata as the fundamental element to provide a better representation of the informational resources available on the Web, and their.